2008
DOI: 10.1051/dst:2007015
|View full text |Cite
|
Sign up to set email alerts
|

Cheeses of Turkey: 3. Varieties containing herbs or spices

Abstract: -Ripened cheese varieties containing herbs are traditional in Turkey and have been manufactured for more than 200 years in the east and southeast of the country. They are manufactured from raw milk, semi-hard in texture and salty in taste and have the aroma of garlic or thyme due to added herbs. Twenty-five types of herb, including Allium, Thymus, Silene and Ferula species which are most popular, are used individually or as appropriate mixtures. The most popular of these cheeses is Otlu which is produced mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
0
25
0
5
Order By: Relevance
“…Higher levels of terpenes in Van Otlu cheese resulted from the manufacturing practices as the addition of some special herbs, including Allium, Thymus, Silene, and Ferula species individually or as appropriate mixtures in the manufacture of this type of cheese, is common. [12] Canak cheese also differed from the other cheeses by being associated with high levels of esters and acids; but it was closely located on the plot with Van Otlu. The cheese is ripened in earthenware pots underground for a long period (probably 1 year) and it is characterized by a sharp and piquant taste due to high levels of lipolysis.…”
Section: Principal Component Analysismentioning
confidence: 88%
“…Higher levels of terpenes in Van Otlu cheese resulted from the manufacturing practices as the addition of some special herbs, including Allium, Thymus, Silene, and Ferula species individually or as appropriate mixtures in the manufacture of this type of cheese, is common. [12] Canak cheese also differed from the other cheeses by being associated with high levels of esters and acids; but it was closely located on the plot with Van Otlu. The cheese is ripened in earthenware pots underground for a long period (probably 1 year) and it is characterized by a sharp and piquant taste due to high levels of lipolysis.…”
Section: Principal Component Analysismentioning
confidence: 88%
“…It was reported that the use of different herbs and their level significantly influence the chemistry, biochemistry and sensory characteristics of Otlu cheese. The manufacturing technology and its characteristics were reviewed extensively by Hayaloglu and Fox [31].…”
Section: Otlu Cheese (Herby Cheese)mentioning
confidence: 99%
“…Much information on technological properties and manufacturing protocols of the Otlu cheese are available in literature (Tuncturk and Coskun ; Tarakci et al . ; Coskun ; Hayaloglu and Fox ; Tarakci and Temiz ). However, there is no report on biological activities and aroma compounds of the herbs added Van Otlu cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Dill, chervil, chives, sage, red pepper, parsley, garlic, tarragon, onion, thyme, anise, caraway and black cumin are among these flavoring materials (Tarakci and Temiz 2008). Much information on technological properties and manufacturing protocols of the Otlu cheese are available in literature (Tuncturk and Coskun 2002;Tarakci et al 2004;Coskun 2005;Hayaloglu and Fox 2008;Tarakci and Temiz 2008). However, there is no report on biological activities and aroma compounds of the herbs added Van Otlu cheese.…”
Section: Introductionmentioning
confidence: 99%